Insight on the Double‐Edged Sword Role of Water Molecules in the Anode of Aqueous Zinc‐Ion Batteries. Issue 12 (23rd September 2022) - Yu, Huaming; Chen, Dongping; Zhang, Tianyun; Fu, Meng; Cai, Jinhao; Wei, Weifeng; Ji, Xiaobo; Chen, Yuejiao; Chen, Libao
Abstract : As promising candidates for aqueous metal batteries, aqueous zinc‐ion batteries (ZIBs) have attracted more attention due to their superior safety, low cost, and environmentally benign characteristics. Solvent water plays a double‐edged sword role that cannot be ignored in the electrochemical performance and long cycling stability of the batteries. The hydrated zinc ions of the solvated structure can boost the diffusion kinetics of zinc ions, whereas the released active water molecules during desolvation can lead to notorious hydrogen evolution reactions, dendrites growth, and surface passivation at the unstable interface between the electrolyte and the anode. Unlike previous reports that summarize recent research progress, this review focuses on the double‐edged sword role of water molecules in the anode during electrochemical processes in ZIBs. The influencing mechanism of water molecules on the stability of zinc anode during the energy storage process is systematically discussed, including the basic theory, water regulation strategies, and recent reports. The two‐faced identity of the water molecules in aqueous electrolyte is profoundly revealed herein, and some revelatory insights and possible strategies are provided for the future design on stable and durable zinc anodes of high‐performance ZIBs. Abstract : This review focuses on the double‐edged sword role of water molecules in the anode during electrochemical processes in zinc‐ion batteries. The influencing mechanism of water molecules on the stability of zinc anode during the energy storage process is systematically discussed. Finally, some revelatory insights and possible strategies are provided for the future design on stable and durable zinc anodes.